Description of Tamerlane in "Tamburlaine the Conqueror" by Hilda Hookham - Sayidova Shahrizoda Nasrulloyevna (Periodica Journal, 2024)
The following article takes a deep dive into the character of Tamerlane in the book of “Tamburlaine the Conqueror” by an English writer Hilda Hookham and analyses how the author portrayed historical figure Amir Temur who was multifaceted, enigmatic historical character. The portrayal of Tamerlane by Hilda Hookham in "Tamburlaine the Conqueror" encapsulates the spirit of this complicated and fascinating historical figure. Through her vivid descriptions and nuanced characterization, she brings Tamerlane to life on the pages of her work, painting a multifaceted portrait of a man.
Keywords: Tamerlane’s character; historical figure; culture